UPAYA MENINGKATKAN KEPEDULIAN LINGKUNGAN SISWA SEKOLAH DASAR MELALUI PROGRAM MANAJEMEN SAMPAH DI SEKOLAH - Astuti, Rini; Liza, Nova; Zurhidayati, Zurhidayati; Fazis, Muhammad (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
This research aims to describe the program of plastic and non-plastic waste management implemented at SDN 13 Muaro to build environmental care character on students. This study using descriptive qualitative, Informants involved in this study include the principal, educators, students, and parents. Data collection was carried out through interviews, observations, and documentation. Meanwhile, the Miles and Huberman model was used as a data analysis technique. The results of the study showed that students' caring character for the environment was already visible in their daily habits at school. On the other hand, the school strengthened the program through teacher training, school campaigns, program integration in the curriculum, supporting facilities, and collaboration with stakeholders. This article is expected to provide insight into the plastic and non-plastic waste management program in elementary schools to increase environmental awareness.